2003
DOI: 10.5466/ijoms.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Immunization with P. gingivalis Surface Protein Antigen and Cholera Toxin Adjuvant Induces T Helper 2 Responses in Both Mucosal and Systemic Compartments

Abstract: It is well establishedthat Porphyromonas gingivalisis one of the major pathogens of adult periodontitis. P. gingivalis produces an outer membrane protein with a molecular mass of 40-kDa (40k-OMP). In the present study, in order to assess the potential for application of 40k-OMP in the development of an antiperiodontal disease vaccine, we analyzed 40k-OMP-specific CD4+ T helper (Th) cell responses induced in the mucosal as well as systemic compartments when 40k-OMP was administered nasally. When CD4+T cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Normally, protein antigen given via the mucosal route without adjuvant has been generally reported to be only a weak immunogen (28, 45–47) and therefore, has been presumed to require a mucosal adjuvant such as CT to induce antigen‐specific antibody responses (28, 31, 45, 47). Our previous findings also indicated that nasal delivery of 40k‐OMP with CT as an adjuvant induced 40k‐OMP‐specific Th2‐type responses that in turn led to the induction of serum IgG and IgA as well as salivary IgA antibodies (30, 31). Despite its efficacy, however, CT is unsuitable for use in humans because it causes severe diarrhea (37).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Normally, protein antigen given via the mucosal route without adjuvant has been generally reported to be only a weak immunogen (28, 45–47) and therefore, has been presumed to require a mucosal adjuvant such as CT to induce antigen‐specific antibody responses (28, 31, 45, 47). Our previous findings also indicated that nasal delivery of 40k‐OMP with CT as an adjuvant induced 40k‐OMP‐specific Th2‐type responses that in turn led to the induction of serum IgG and IgA as well as salivary IgA antibodies (30, 31). Despite its efficacy, however, CT is unsuitable for use in humans because it causes severe diarrhea (37).…”
Section: Discussionmentioning
confidence: 80%
“…Since mucosal (e.g. nasal or oral) administration of CT with soluble protein has proven to be an effective regimen for the generation of antigen‐specific antibody responses (20, 28, 30, 45, 47), we next examined the effect of the transcutaneous administration of CT as adjuvant on 40 K‐OMP‐specific antibody responses. Rats transcutaneously immunized with 40k‐OMP plus CT showed almost the same 40k‐OMP‐specific serum IgG and IgA responses as those immunized with 40k‐OMP alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…18 P. gingivalis and F. nucleatum have an outer membrane protein with a molecular mass of 40-kDa. 19 Against this background, the research aim was to determine whether IgY anti A. actinomycetemcomitans and P. gingivalis can be employed to inhibit colonization of F. nucleatum and S. sanguinis bacteria.…”
Section: Introductionmentioning
confidence: 99%